Revealing a gap in the clinical competence of nursing staff in nursing homes: a cross-sectional study with the Ms. Olsen test - Irén Vikström-Dahl; Pia Cecile Bing-Jonsson; Auvo Rauhala; Lisbeth Fagerström (BMC, 2023)
Abstract Background Nursing staff, caring for frail older people in long-term care, needs to have a certain level of clinical competence to identify diseases at an early stage and to assess and provide good nursing care. In Finland, nursing care is based on evidence-based and high-quality nursing care. However, earlier inspections by the National Supervisory Authority for Welfare and Health showed many discrepancies between the nursing staff's clinical competence and adequate and continuous education. Aim This study aimed to explore nursing staff, i.e. the clinical competence and decision-making skills of registered and practical nurses in nursing homes for older people in Finland and to analyse the association between nurses' clinical competence and fundamental background factors. Methods We conducted a cross-sectional study of 337 participants in 50 nursing homes in the western part of Finland, between December 2020 and January 2021. The instrument used was the validated Ms. Olsen test, an extraction of NOP-CET. Statistical analyses were conducted with descriptive statistics and correlations and a cut-off for clinical competence. Results This study with the Ms. Olsen test revealed that only one-fourth of the RNs and a third of the PNs passed the clinical competence test. In the self-evaluation, almost all participants evaluated themselves with good clinical competence. The Finnish Current Care Guidelines were used on a daily basis by 7.4% and weekly by 30%. Significant correlation was found between Swedish as a working language and mother tongue and the score for clinical competence. Conclusion The clinical competence test, the Ms. Olsen test, was used in Finland for the first time to evaluate the nursing staffs´ clinical competence in nursing homes. We found gaps in the clinical competence in Finnish nursing homes, both for PNs and RNs. The result differed remarkably from their self-assessments and the staff did not use the national nursing guidelines as required to develop their nursing skills and knowledge. Gaps in the clinical competence have been identified and can be used to develop targeted continuous education.